PHOTOCHEMICAL TEST AND REPELLENT VIRGIN COCONUT OIL (VCO) TEST WITH SUPLEMENTATION OF Citronella Oil - i wayan karta (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Background: Repellents are chemicals or non-chemicals that can prevent insect activity from approaching humans. The development of repellent products needs to be done so as not to cause skin irritation and provide skin health. The purpose of this study was to carry out phytochemical and repellent tests to determine the active content and effectiveness of virgin coconut oil (VCO) supplementation with Citronella oil (CO) repellent essential oil against Aedes aegypti mosquitoes. Method: The research method used was true experiment with Posttest Only Control Group Design with experimental group namely VCO, VCO supplementation with 10% and 20% CO. Results: VCO supplementation with CO contained flavonoids, alkaloids, tannins, terpenoids, and saponins. VCO has a repellant power of 68.47%, supplementation with a combination of VCO with CO 10% is 97.55% and a concentration of 20% is 100%. Conclusion: VCO and CO supplementation of 10% and 20% were effective as repellants against Aedes aegypti mosquitoes. These two concentrations did not have a significant difference, so the 10% concentration could be used as the basis for further research. The presence of active ingredients in VCO supplementation with CO provides potential as a repellant and skin health care.. Suggestion: Organoleptic testing on this supplementation repellent product needs to be done so that it can be used by the community..